In Silico studies of novel Sildenafil self-emulsifying drug delivery system absorption improvement for pulmonary arterial hypertension - BARBÁRA A. ABRAHIM-VIEIRA; ALESSANDRA M.T. DE SOUZA; RITA C. BARROS; FLÁVIA A. DO CARMO; LETÍCIA C.L. DE ABREU; RONYSON S.S. MOREIRA; THIAGO S. HONÓRIO; CARLOS R. RODRIGUES; VALERIA P. DE SOUSA; LUCIO M. CABRAL (Anais da Academia Brasileira de Ciências, 2020)
Abstract Sildenafil is a potent selective inhibitor of phosphosdiesterase-5 previously used in erectile dysfunction and subsequently approved in 2005 for pulmonary arterial hypertension treatment. Since oral administration of sildenafil shows pharmacokinetic problems with mean absolute bioavailability of 41%, the goal of this work was to develop a novel sildenafil self-emulsifying drug delivery system (SEDDS) for oral absorption improvement and management of dosage. One pharmaceutical solution and four SEDDS containing sildenafil were successfully obtained and SEDDS formed O/W nanoemulsion with droplet size less than 300 nm. The stability studies evidenced that the SEDDS containing 3.3% w/w of sildenafil yielded the best results. The safety of 2-pyrrolidone/isobutanol in oral formulations was assessed in mice and no lethality was achieved in the placebo groups with LD50 of 490 mg/Kg for SEDDS II-3.3, suggesting it as a safe excipient for humans. Therewithal, in silico studies using PBPK models provided the pharmacokinetic profile of sildenafil SEDDS. Subsequently, in silico evaluation indicated that the sildenafil SEDDS droplet size influenced its bioavailability, enhancing absorption, assuring a good pharmacokinetic profile. These findings suggest that the formulations developed here presented the potential to enhance drug oral absorption with the possibility to control drug dosage as they are liquid pharmaceutical formulations.